Activity Theory: An Analysis of Students’ Demotivation Factors due to Zoning Policy Implementation in Sleman, Bantul, and Yogyakarta Region - Arsanto, Albertus Yordhana; Budiraharjo, Markus (LPPM Universitas Mercu Buana Yogyakarta, 2019)
Zoning policy has become a new regulation in New Student Admission (PPBD) at Yogyakarta Province, such as Sleman, Yogyakarta, and Bantul district. The research focuses on students’ demotivation factors due to the new regulation implemented by the government about zoning system. The research uses the semi-structured interview for eighteen students from different cities and two students chosen and analyzed by Activity Theory and they are from different school and district. The result is that the students feel demotivated, since the factors are their favorite schools, classmates, teachers, and the regulation itself. The most affecting factor is their classroom environment owing to the diverse students in the classroom. However, the students try to adapt the environment in order to enhance their learning experience and motivation.